Primary homework in England: the beliefs and practices of teachers in primary schools - Medwell, Jane A.; Wray, David J. (Taylor & Francis, 2018)
This study examines teachers’ views about and practices in homework in primary schools, based on questionnaire data from 235 primary teachers and 19 in-depth interviews. Findings suggest that teachers prioritise contradictory goals and act in ways that support only some of these. Reading with parents is a universal form of homework and other homework focuses either on English or mathematics or takes a project-led approach. Integration of homework into class learning is problematic. Teachers are concerned about the possible effects of homework on educational inequality and questions are raised about teachers’ perceptions of homework as a signifier of good parenting.